Rancang Bangun Media Konseling Pastoral Berbasis Facebook Fanpage - Manufuri, Jerson (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
The phenomenon of the COVID-19 pandemic which has an impact on social change in society is increasingly being felt by all groups in various aspects of life. During the new normal period, people are required to continue to implement physical distancing to suppress the spread of COVID-19. This social impact provides space for every community, especially counselors, to continue to think creatively and innovatively in utilizing digital in this modern civilization, for the sake of continuity of pastoral counseling services which creates a tendency for an open society paradigm, namely there are no barriers that prevent counselors and clients from mutually interact. This research aims to design and design as much as possible a facebook fanpage-based pastoral counseling media to be utilized for the continuity of counseling in the present. The research method used is narrative qualitative with the following steps: describing the basic concepts of online pastoral counseling, introducing the stages of creating a Facebook fanpage, and providing an overview of how to design Christian-based content for the benefit of counselors and counselees. The result of this research is to produce a pastoral counseling media product based on Facebook fanpage which can be used for the online pastoral counseling process by working on the features in it.